RISK ASSESSMENT ALAT PRODUKSI GULA CANE KNIFE PADA STASIUN GILINGAN DI PT. X - Bramantio Andananta Chrisna Putra (Universitas Airlangga, 2018)
Industrial development in Indonesia is growing rapidly. This should be balanced with the application of good HA safety risk management to workplace hazard risks. As in PT. X Lumajang Regency, in its production process has great potential hazard. One of them is in the cane knife tool at Gilingan Station that has been damaged in operation and has an employee accident impact. Therefore, to prevent the occurrence of recurrence of risk assessment, including hazard identification, risk assessment and hazard control. The purpose of this study is to conduct risk assessment using the method of failure mode effect analysis (FMEA) on the Cane Knife production process tool in PT. X Lumajang District. This research is descriptive research. The target of this research is sugar production process at PT. X with the informant is 1 person Quality Control (QC), 1 person production operators and 1 supervisor. The results show that there are 6 (six) failure modes that occur in the cane knife tool. Based on the Risk Priority Number (RPN), the highest failure mode occurs is a broken clutch string. While for risk control, quite enough. This is because there have been risk control efforts include technical control that is the installation of safety valve, administrative control is the application of SOP for workers and personal protective equipment. But for personal protective equipment only safety helmet, for other companies do not provide. The conclusion that can be drawn is the need for better risk control, especially on the damage that occurred on the clutch rope broken tool cane knife.Keywords: cane knife, failure mode effect analysis, risk assessment